Effect of the inclusion of static stretching in general warming up on muscle strength in Brazilian army military personnel - Michel Moraes Gonçalves; Wilian de Paula Walter; Luiz Guilherme da Silva Pinto; Adalgiza Moreno Mafra; Paulo Henrique Moura; Runer Augusto Marson; Humberto Lameira Miranda (Motriz: Revista de Educacao Fisica, 2021)
Abstract Aim: Several health professionals prescribe static stretching exercises (SS) as essential for those that practice physical exercises, for injury prevention and performance improvement, although there is still no consensus. There are few studies on the effects of SS use on warming up. Thus study aimed to compare the effects of the inclusion of SS in general warming up procedures on muscle strength in Brazilian army personnel. Methods: Thirty-two young military men were selected. They were subjected to anthropometric evaluation and performed knee extension and flexion in an isokinetic digital dynamometer, at a speed of 60°/s. Then, they were divided into two randomized and counterbalanced groups, Traditional Group (TG) and Experimental Group (EG). The TG performed the lower limbs warm-up protocol provided for military physical training (MPT) and immediately after, performed the isokinetic muscle strength test. The EG performed the same protocol, performing the SS in the hamstrings and quadriceps, before warming up. Results: An increase was found in the peak isokinetic torque in the knee extension of the EG (Pre: 209.80 ± 21.36 vs Post: 243.98 ± 30.35; p = 0.001) and flexion (Pre: 130.86 ± 18.63 vs Post: 142.41 ± 25.92; p = 0.006). In the TG, significant differences were found in the extension of the knee, but not in flexion (Pre: 209.14 ± 34.27 vs. Post: 239.38 ± 36.17; p = 0.001 and Pre: 129.23 ± 18.43 vs Post: 133.66 ± 13.20; p = 0.297, respectively). Conclusion: The inclusion of SS in general warming up did not harm and even improved muscle strength performance in knee extension and flexion in Brazilian Army military personnel.